The Development of Two-Tier Multiple Choice Test to Assess Students’ Conceptual Understanding about Light and Optical Instruments - Widiyatmoko, A.; Shimizu, K. (Jurnal Pendidikan IPA Indonesia, 2018)
This study aimed to develop a two-tier multiple choice test about the concept of Ã¢â‚¬Å“light and optical instrumentsÃ¢â‚¬Â in 8th grade of Indonesian science curriculum. The test development procedure had three general steps: defining the content area of the test, identification on studentsÃ¢â‚¬â„¢ conceptions, and the development of two-tier multiple choice test. The final version of two-tier multiple choice test consisted of 25 items question. This test was administered to 95 junior high school students. The students had completed a unit on light and optical instruments. The reliability of the test was 0.76. Based on the data analysis, twenty-two alternative conceptions were identified. The results of the study showed that the two-tier multiple choice test was effective in determining the studentsÃ¢â‚¬â„¢ misconceptions and also it might be used as an alternative to the traditional multiple choice test. In conclusion, two-tier multiple choice test can be used to assess studentsÃ¢â‚¬â„¢ conceptual understanding as well as studentsÃ¢â‚¬â„¢ misconceptions on light and optical instruments concept.